Convexity preserving summability matrices - C. R. Selvaraj (International Journal of Mathematics and Mathematical Sciences)
The main result of this paper gives the necessary and sufficient conditions for the Abel matrices to preserve the convexity of sequences. Also, the higher orders of the Cesáro method are shown to be convexity-preserving matrices.